Defective metal organic framework catalyst mutated by persulfate etching, and preparation method and application thereof

By vapor deposition method on metal organic framework materials combined with persulfate etching, defective structures are formed, and a functionalized "defective" metal organic framework catalyst is prepared, which solves the insufficient catalyst stability and low catalytic efficiency in catalytic oxidation reaction. and realizes efficient recovery of catalysts and industrial applications.

CN119456033AActive Publication Date: 2025-02-18ZHEJIANG UNIV OF TECH +1
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411589337.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-02-18
Estimated Expiration
2044-11-08

AI Technical Summary

Technical Problem

The existing pure metal organic framework (MOFs) catalysts have problems such as insufficient stability and low catalytic efficiency in catalytic oxidation reactions, and doping defective catalysts have problems such as small material scale, difficulty in recycling and mass production in practical applications.

Method used

The metal organic framework material MIL-53 (Fe) or Cu-BTC was synthesized by hydrothermal method, and then the vapor deposition method combined with persulfate etching was used to form defect structures to prepare a functionalized "defective" metal organic framework heterogeneous phase catalyst.

Benefits of technology

This method solves the problems of the stability and catalytic efficiency of the catalyst, realizes efficient catalysis of tetracycline hydrochloride, and the catalyst can be recovered through simple physical methods, with good industrial application potential.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure HDA0005125149780000011
    Figure HDA0005125149780000011
Patent Text Reader

Abstract

The invention discloses a defect type metal organic framework catalyst mutated by persulfate etching as well as a preparation method and application of the defect type metal organic framework catalyst. The method comprises the following steps: putting a metal organic framework material and persulfate into a reaction container, vacuumizing, introducing inert gas, carrying out chemical vapor deposition reaction at 120-180 DEG C for 3-12 hours, washing an obtained solid product with pure water and ethanol, and drying to obtain the persulfate etching mutagenesis defect type metal organic framework catalyst, the TOFs of the material to tetracycline hydrochloride can reach 1.847 h <-1 > by regulating and controlling the preparation conditions, the preparation process is simple, the material performance is excellent, and the material has a wide application prospect in the field of catalytic oxidation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a functional defective catalytic material and a preparation method and application thereof, and in particular to a persulfate etching-induced "defective" metal organic framework (MOFs) catalyst and a vapor deposition modification method thereof, as well as an application thereof in catalytic oxidation reactions. Background Art

[0002] Catalytic oxidation technology has been widely used in energy supply, pharmaceutical chemicals, agriculture, handicrafts, environmental protection and other fields. MOFs, as a catalytic material with customizable channel structure, large surface area and multifunctionality, has attracted much attention in the field of catalytic oxidation technology. However, the disadvantage of pure MOFs is that the electron-hole pairs undergo rapid recombination, resulting in limited collection or insufficient stability, which hinders the improvement of catalytic efficiency. Therefore, modifying pure MOFs catalysts to improve their catalytic performance has become the key to accelerating catalytic oxidation reactions.

[0003] At present, antibiotics are widely used in the prevention and treatment of human and animal diseases, as well as in animal feed additives. Antibiotics have the characteristics of complex composition, stable structure and difficulty in degradation. Most traditional water treatment technologies still cannot meet the national emission standards for the removal of pollutants such as antibiotics. Therefore, the removal of antibiotics in the water environment has become increasingly urgent, and the development of economical, efficient, and environmentally friendly antibiotic treatment technologies is of great significance. The current commonly used method for degrading organic pollutants in water is to use advanced oxidation technology (AOPs), which is a type of technology that uses hydroxyl radicals as active oxygen species to oxidize and degrade organic matter in water. It mainly includes Fenton, photo (electro) Fenton, ozone oxidation, wet oxidation, etc. Among them, the Fenton reaction uses H2O2 as the oxidant and Fe 2+ The catalyst generates hydroxyl radicals, which can oxidatively degrade low-concentration organic pollutants at room temperature and pressure. Therefore, it is crucial to select a catalyst that is suitable for a better pH application range, has higher selectivity for target pollutants, and has a longer half-life.

[0004] Due to the limitations of pure MOFs materials, defective materials formed by doping have emerged in recent research. Patent documents CN113617350A and CN114824223A respectively use plasma etching of carbon materials to obtain defective carbon materials and use N-doped carbon microspheres as templates to achieve surface defects and high sulfur defect vacancies in materials; patent documents CN115090299A and CN114959636A treat ZIS prepared by hydrothermal method with a reducing agent to prepare ZIS semiconductor photocatalytic materials with S defects and use vapor deposition method to prepare two-dimensional transition metal sulfides. Although defective materials have been widely used as catalysts in theoretical research, there are still many problems that need to be urgently solved in actual use: (1) Most of the defective doped catalysts reported so far are C-based materials. Due to the limitations of the materials themselves, the catalytic effect is limited; (2) Most of the defective doped catalysts reported so far are etched by inorganic substances such as MnS, ZIS, etc. The materials themselves are small in size, and it is difficult to produce and recycle them on a large scale by vapor deposition method. Similar semiconductor materials have low value enhancement and limited application range. These drawbacks have seriously limited the widespread application of defect-doped catalysts in the field of catalysis. Summary of the invention

[0005] The present invention aims to provide a functionalized "defective" metal organic framework heterogeneous catalyst for catalytic oxidation reaction and a preparation method thereof. The present invention first synthesizes metal organic framework materials MIL-53 (Fe) and Cu-BTC by hydrothermal method, and then forms defect structures on the surface of MOFs by means of vapor deposition combined with persulfate etching.

[0006] The present invention solves the problems of existing defective doped materials being small in size, difficult to recycle and economical in mass production, and utilizes a chemical vapor deposition method to perform persulfate etching modification, thus providing a method for the modification of MOFs catalysts.

[0007] The technical solution of the present invention is as follows:

[0008] A method for preparing a "defective" metal organic framework catalyst induced by persulfate etching, comprising:

[0009] Putting a metal organic framework material (MOFs) and persulfate into a reaction container, evacuating the container and introducing an inert gas, performing a chemical vapor deposition reaction at 120-180° C. for 3-12 hours, washing the obtained solid product with pure water and ethanol, and drying the solid product to obtain the persulfate-etched "defective" metal organic framework catalyst;

[0010] in,

[0011] The metal center of the metal organic framework material is Fe, Cu, or a mixture of the two in any proportion. Specific metal organic framework materials include: MIL-53 (Fe) or Cu-BTC;

[0012] The persulfate is selected from one of potassium persulfate, sodium persulfate, and ammonium persulfate, or a mixture of two or more of them in any proportion;

[0013] The mass ratio of the metal organic framework material to the persulfate is 1:0.5-5, preferably 1:2;

[0014] The inert gas can be nitrogen or argon, with a ventilation volume of 50-80 cm / s;

[0015] The preferred chemical vapor deposition temperature is 150° C. and the time is 6 h.

[0016] During the chemical vapor deposition process of the present invention, at a high temperature of 120 to 180°C, persulfate undergoes thermal decomposition to release sulfur dioxide (SO2) gas, which reacts chemically with the metal surface, resulting in metal etching and the formation of oxygen vacancies. The etching mechanism of SO2 involves reaction with metals to generate metal sulfides. And along with the gas flow, part of the sulfate can also chemically etch the MOF surface.

[0017] The invention relates to a "defective" metal organic framework catalyst induced by persulfate etching prepared by the preparation method.

[0018] The persulfate-etching-induced "defective" metal organic framework catalyst of the present invention can be used in catalytic oxidation reactions, for example, for catalyzing the oxidation degradation of tetracycline hydrochloride by hydrogen peroxide.

[0019] Compared with the prior art, the advantages of the present invention are:

[0020] 1. Doping non-metallic materials such as sulfur on the surface and pores of metal organic framework materials by chemical vapor deposition (which can be repeated), and inducing mutations by changing the temperature and gas flow during the vapor deposition process to obtain defective morphological structures, which provides a way of thinking for doping materials and expands the application field of metal organic framework catalysts.

[0021] 2. By adjusting the preparation conditions, the TOFs of the metal organic framework catalyst for tetracycline hydrochloride can reach 1.847h -1 The invention has a simple preparation process and excellent material performance, and has broad prospects in the field of catalytic oxidation applications.

[0022] 3. The catalyst can be recovered by simple physical methods such as centrifugation and filtration, which is energy-saving and environmentally friendly, and has good effects of multiple reuses, and has great potential for industrial application. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 : SEM image of embodiment 7 of the present invention.

[0024] Figure 2 : TEM image of Example 7 of the present invention.

[0025] Figure 3 : FTIR graphs of Example 7 of the present invention and Comparative Example 1.

[0026] Figure 4 : XRD diagrams of Example 7 of the present invention and Comparative Example 1. DETAILED DESCRIPTION

[0027] The present invention is described in detail below in conjunction with specific embodiments, but the present invention is not limited to the following embodiments. Without departing from the content and scope of the present invention, changes in implementation should be included in the technical scope of the present invention.

[0028] Example 1

[0029] 0.2 g MIL-53 (Fe) and 0.1 g sodium persulfate were placed in a polytetrafluoroethylene reactor at a mass ratio of 1:0.5. After vacuuming, argon gas was introduced at 120°C for chemical vapor deposition reaction for 6 hours. Then, the reactor was washed with water and ethanol three times respectively, centrifuged, and dried at 60°C for 12 hours to obtain Fe-based MOFs with S-doped mutation of rosette skeleton structure (hereinafter referred to as Sps-MIL-53 (Fe) (Na)-0.5 to represent the carrier).

[0030] Example 2

[0031] 0.2 g of MIL-53 (Fe) and 0.2 g of sodium persulfate were placed in a polytetrafluoroethylene reactor in a mass ratio of 1:1, and argon gas was introduced at 120°C for chemical vapor deposition reaction for 6 hours. Then, they were washed with water and ethanol three times respectively, centrifuged, and dried at 60°C for 12 hours to obtain Fe-based MOFs with S-doped mutations having a rose skeleton structure (hereinafter referred to as Sps-MIL-53 (Fe) (Na)-1 to represent the carrier).

[0032] Example 3

[0033] 0.1 g of MIL-53 (Fe) and 0.2 g of sodium persulfate were placed in a polytetrafluoroethylene reactor at a mass ratio of 1:2, and argon gas was introduced at 120°C for chemical vapor deposition reaction for 6 hours. Then, the mixture was washed with water and ethanol three times respectively, centrifuged, and dried at 60°C for 12 hours to obtain Fe-based MOFs with S-doped mutations having a rosette skeleton structure (hereinafter referred to as Sps-MIL-53 (Fe) (Na)-2 to represent the carrier).

[0034] Example 4

[0035] 0.1 g of MIL-53 (Fe) and 0.3 g of sodium persulfate were placed in a polytetrafluoroethylene reactor at a mass ratio of 1:3, and argon gas was introduced at 120°C for chemical vapor deposition reaction for 6 hours. Then, the mixture was washed with water and ethanol three times respectively, centrifuged, and dried at 60°C for 12 hours to obtain Fe-based MOFs with S-doped mutation of rosette skeleton structure (hereinafter referred to as Sps-MIL-53 (Fe) (Na)-3 to represent the carrier).

[0036] Example 5

[0037] 0.1 g of MIL-53 (Fe) and 0.4 g of sodium persulfate were placed in a polytetrafluoroethylene reactor at a mass ratio of 1:4, and argon gas was introduced at 120°C for chemical vapor deposition reaction for 6 hours. Then, the mixture was washed with water and ethanol three times respectively, centrifuged, and dried at 60°C for 12 hours to obtain Fe-based MOFs with S-doped mutation of rosette skeleton structure (hereinafter referred to as Sps-MIL-53 (Fe) (Na)-4 to represent the carrier).

[0038] Example 6

[0039] 0.1 g of MIL-53 (Fe) and 0.5 g of sodium persulfate were placed in a polytetrafluoroethylene reactor at a mass ratio of 1:5, and argon gas was introduced at 120°C for chemical vapor deposition reaction for 6 hours. Then, the mixture was washed with water and ethanol three times respectively, centrifuged, and dried at 60°C for 12 hours to obtain Fe-based MOFs with S-doped mutations having a rose skeleton structure (hereinafter referred to as Sps-MIL-53 (Fe) (Na)-5 to represent the carrier).

[0040] Example 7

[0041] 0.1 g of MIL-53 (Fe) and 0.2 g of sodium persulfate were placed in a polytetrafluoroethylene reactor at a mass ratio of 1:2, and argon gas was introduced at 150°C for chemical vapor deposition reaction for 6 hours. Then, the mixture was washed with water and ethanol three times respectively, centrifuged, and dried at 60°C for 12 hours to obtain Fe-based MOFs with S-doped mutation of rosette skeleton structure (hereinafter referred to as Sps-MIL-53 (Fe) (Na) -150 to represent the carrier).

[0042] Example 8

[0043] 0.1 g of MIL-53 (Fe) and 0.2 g of sodium persulfate were placed in a polytetrafluoroethylene reactor at a mass ratio of 1:2, and argon gas was introduced at 180°C for chemical vapor deposition reaction for 6 hours. Then, the mixture was washed with water and ethanol three times respectively, centrifuged, and dried at 60°C for 12 hours to obtain Fe-based MOFs with S-doping mutation of rosette skeleton structure (hereinafter referred to as Sps-MIL-53 (Fe) (Na) -180 to represent the carrier).

[0044] Example 9

[0045] 0.1 g of MIL-53 (Fe) and 0.2 g of sodium persulfate were placed in a polytetrafluoroethylene reactor at a mass ratio of 1:2, and argon gas was introduced at 150°C for chemical vapor deposition reaction for 3 hours. Then, the mixture was washed with water and ethanol three times respectively, centrifuged, and dried at 60°C for 12 hours to obtain Fe-based MOFs with S-doping mutation of rosette skeleton structure (hereinafter referred to as Sps-MIL-53 (Fe) (Na)-3h to represent the carrier).

[0046] Example 10

[0047] 0.1 g of MIL-53 (Fe) and 0.2 g of sodium persulfate were placed in a polytetrafluoroethylene reactor at a mass ratio of 1:2, and argon gas was introduced at 150°C for chemical vapor deposition reaction for 9 hours. Then, the mixture was washed with water and ethanol for 3 times respectively, centrifuged, and dried at 60°C for 12 hours to obtain Fe-based MOFs with S-doping mutation of rosette skeleton structure (hereinafter referred to as Sps-MIL-53 (Fe) (Na)-9h to represent the carrier).

[0048] Embodiment 11

[0049] 0.1 g of MIL-53 (Fe) and 0.2 g of sodium persulfate were placed in a polytetrafluoroethylene reactor at a mass ratio of 1:2, and argon gas was introduced at 150°C for chemical vapor deposition reaction for 12 hours. Then, the mixture was washed with water and ethanol three times respectively, centrifuged, and dried at 60°C for 12 hours to obtain Fe-based MOFs with S-doped mutation of rosette skeleton structure (hereinafter referred to as Sps-MIL-53 (Fe) (Na)-12h to represent the carrier).

[0050] Example 12

[0051] 0.1 g Cu-BTC and 0.2 g sodium persulfate were placed in a polytetrafluoroethylene reactor in a mass ratio of 1:2, and argon gas was introduced at 150°C for chemical vapor deposition reaction for 9 hours. Then, the phases were washed with water and ethanol for 3 times respectively, centrifuged, and dried at 60°C for 12 hours to obtain a Cu-based material (Aps-Cu-BTC(Na)) with a S-doped defective blue rose skeleton structure.

[0052] Embodiment 13

[0053] 0.1 g of MIL-53 (Fe) and 0.2 g of potassium persulfate were placed in a polytetrafluoroethylene reactor at a mass ratio of 1:2, and argon gas was introduced at 150°C for chemical vapor deposition reaction for 6 hours. Then, the mixture was washed with water and ethanol three times respectively, centrifuged, and dried at 60°C for 12 hours to obtain Fe-based MOFs with S-doped mutations having a rosette skeleton structure (hereinafter Sps-MIL-53 (Fe) (K) is used to represent the carrier).

[0054] Embodiment 14

[0055] 0.1 g of MIL-53 (Fe) and 0.2 g of ammonium persulfate were placed in a polytetrafluoroethylene reactor at a mass ratio of 1:2, and argon gas was introduced at 150°C for chemical vapor deposition reaction for 6 hours. Then, the mixture was washed with water and ethanol three times respectively, centrifuged, and dried at 60°C for 12 hours to obtain Fe-based MOFs with S-doped mutations having a rosette skeleton structure (hereinafter Sps-MIL-53 (Fe) (NH4) is used to represent the carrier).

[0056] Embodiment 15

[0057] 0.1 g of MIL-53 (Fe) and 0.2 g of sodium persulfate were placed in a polytetrafluoroethylene reactor at a mass ratio of 1:2, and nitrogen was introduced at 150°C for chemical vapor deposition reaction for 6 hours. Then, the mixture was washed with water and ethanol three times respectively, centrifuged, and dried at 60°C for 12 hours to obtain Fe-based MOFs with S-doped mutation of rosette skeleton structure (hereinafter Sps-MIL-53 (Fe) (Na) -N2 is used to represent the carrier).

[0058] Comparative Example 1 Preparation of MIL-53 (Fe)

[0059] Put 1.663g of terephthalic acid and 1.350g of ferric chloride hexahydrate into a 50mL polytetrafluoroethylene reactor, add 25mL of N,N-dimethylformamide (DMF), and stir ultrasonically for 10 minutes. Then put the uniform solution into a preheated oven, the reaction temperature is 150°C, the reaction time is 15h, then filter, wash with water, and place in an oven at 80°C to dry for 12h to obtain MIL-53(Fe).

[0060] Comparative Example 2 Preparation of Cu-BTC

[0061] Take trimesic acid (H3BTC, 0.8107 g, 5 mmol) and mix it with 25 ml of dimethyl sulfoxide (DMSO), dissolve it by ultrasonication, then cool the solution and slowly add Cu(NO3)2·3H2O (2.1744 g, 9 mmol), dissolve it by ultrasonication and stir for 30 min to obtain a blue transparent solution, transfer the solution to a 50 ml reactor, heat it at a constant temperature of 120°C for 24 h to obtain Cu-BTC microcrystals.

[0062] Catalyst performance test

[0063] The catalyst materials prepared in Examples 1 to 15 and Comparative Examples 1 and 2 were tested for their catalytic performance in the oxidation degradation of tetracycline hydrochloride by hydrogen peroxide. The test conditions were: hydrogen peroxide concentration 0.5 μL / mL; catalyst input amount: 10 mg / L; tetracycline concentration 50 mg / L. The results are shown in Table 1.

[0064] Table 1 Performance comparison of supported catalysts prepared in Examples 1 to 15 and Comparative Examples 1 and 2

[0065]

[0066]

Claims

1. A method for preparing a "defective" metal organic framework catalyst induced by persulfate etching, characterized in that: The preparation method comprises: Putting the metal organic framework material and persulfate into a reaction container, evacuating the vacuum and introducing an inert gas, performing a chemical vapor deposition reaction at 120-180° C. for 3-12 hours, washing the obtained solid product with pure water and ethanol, and drying, to obtain the persulfate-etched "defective" metal organic framework catalyst; in, The metal center of the metal organic framework material is Fe, Cu, or a mixture of the two in any proportion.

2. The method for preparing a "defective" metal organic framework catalyst induced by persulfate etching as claimed in claim 1, characterized in that: The metal organic framework material is selected from: MIL-53 (Fe) or Cu-BTC.

3. The method for preparing a "defective" metal organic framework catalyst induced by persulfate etching as claimed in claim 1, characterized in that: The persulfate is selected from one of potassium persulfate, sodium persulfate, and ammonium persulfate, or a mixture of two or more of them in any proportion.

4. The method for preparing a "defective" metal organic framework catalyst induced by persulfate etching as claimed in claim 1, characterized in that: The mass ratio of the metal organic framework material to the persulfate is 1:0.5-5.

5. The method for preparing the "defective" metal organic framework catalyst induced by persulfate etching as claimed in claim 4, characterized in that: The mass ratio of the metal organic framework material to the persulfate is 1:

2.

6. The method for preparing a "defective" metal organic framework catalyst induced by persulfate etching as claimed in claim 1, characterized in that: The inert gas is nitrogen or argon, with a ventilation rate of 50 to 80 cm / s.

7. The method for preparing a "defective" metal organic framework catalyst induced by persulfate etching as claimed in claim 1, characterized in that: The chemical vapor deposition temperature was 150°C and the time was 6 h.

8. A "defective" metal organic framework catalyst induced by persulfate etching obtained by the preparation method according to any one of claims 1 to 7.

9. Use of the "defective" metal organic framework catalyst induced by persulfate etching as claimed in claim 8 in catalytic oxidation reactions.

10. The use according to claim 9, characterized in that The persulfate-etching-induced "defective" metal organic framework catalyst is used to catalyze the oxidative degradation of tetracycline hydrochloride with hydrogen peroxide.

Citation Information

Patent Citations

  • Defective carbon material as well as preparation method and application thereof

    CN113617350A

  • MnS / carbon composite material with sulfur defect as well as preparation method and application of MnS / carbon composite material

    CN114824223A

  • Two-dimensional transition metal sulfide and preparation method and application thereof

    CN114959636A

  • Preparation method of ZnIn2S4 photocatalyst with sulfur defect and application of ZnIn2S4 photocatalyst in degradation of antibiotics

    CN115090299A

  • Sulfonic functionalized mesoporous silicon dioxide microsphere loaded metal oxide catalyst and preparation method and application of catalyst

    CN104646033A